Valoración del riesgo de desarrolla diabetes mellitus a través del test de findrisk en la población de la cabecera cantonal del cantón Macará. - Criollo Yaguana, Lizeth Katherine (2017)
Diabetes Mellitus is a set of metabolic alterations of multiple etiology characterized by chronic hyperglycemia and defects in insulin secretion, in the action of the same or in both. In Ecuador, this pathology occupies the second place between the causes of general mortality and the third in mortality in over 65 years. The objectives of the study were to know the main risk factors for developing type 2 diabetes mellitus, to determine the risk according to age, to determine the risk according to gender, and to construct a prevention proposal. It was a quantitative, descriptive, transversal study, being the sample of 362 people of the cantonal head of the canton Macara. The FINDRISK Test was used as a tool to assess the risk of developing diabetes, thus showing a low risk of developing Diabetes Mellitus in 10 years, in 40.6% of the total population, but a 1, 1% present very high risk; Of the participants, 45.3% were overweight, and 46.4% had an abdominal circumference; normal-high, The sedentarism is at 35.9%. Lack of fruit and vegetable consumption in 54.4% of the population. 24.3% presented first-degree relatives with this pathology. It is concluded that the main factors are: overweight, normal-high abdominal perimeter, sedentary lifestyle, and poor diet; being greater the risk between the ages 55 to 64 years, being the predominant gender the feminine one. Key words: Diabetes Mellitus, Risk, Findrisk Test.